Nizatidine interacts with ct-DNA causing genotoxicity and cytotoxicity: an assessment by in vitro, in vivo, and in silico studies. Issue 2 (22nd January 2023) - Rahman, Yusra; Afrin, Shumaila; Perwez, Ahmad; Ansari, Mohd Owais; Sarwar, Tarique; Ahmed, Shahbaz; Rizvi, Moshahid Alam; Shadab, G. G. Hammad A.; Tabish, Mohammad
Abstract: H2 receptor antagonists are the medication given for treating stomach ulcers, but lately, reports have shown their role in healing several malignant ulcers. The present work entails the interaction of H2 blocker nizatidine with calf thymus (ct)-DNA for determining the binding mode and energetics of the interaction. Multi-spectroscopic, calorimetric, viscometric and bioinformatic analysis revealed that nizatidine interacted with ct-DNA via groove-binding mode and is characterised by exothermic reaction. Moreover, assessment of genotoxic potential of nizatidine in vitro was carried out in peripheral human lymphocytes by alkaline comet assay. DNA damage occurred at high concentrations of nizatidine. Genotoxicity of nizatidine was also evaluated in vivo by assessing cytogenetic biomarkers viz. micronuclei formation and chromosomal aberration test. Nizatidine was able to induce micronuclei formation and chromosomal damage at high dose. Additionally, cytotoxic activity of nizatidine was determined in cancer cell lines, namely HeLa and HCT-116 and compared with the normal human cell line HEK-293 employing MTT assay. It was observed that nizatidine was more toxic towards HeLa and HCT-116 than HEK-293. Cell morphology analysis by compound inverted microscopy further strengthens the finding obtained through MTT assay. Graphical Abstract: UF0001 Communicated by Ramaswamy H. Sarma